ZmSTK1 and ZmSTK2, encoding receptor‐like cytoplasmic kinase, are involved in maize pollen development with additive effect - Fan, Mingxia (Plant Biotechnol J, 2018)
Pollen germination and pollen tube growth are important physiological processes of sexual reproduction of plants and also are involved in signal transduction. Our previous study reveals that ZmSTK1 and ZmSTK2 are two receptor‐like cytoplasmic kinases (RLCK) homologs in Zea mays as members of receptor‐like protein kinase (RLK) subfamily, sharing 86% identity at the amino acid level. Here, we report that ZmSTK1 and ZmSTK2, expressed at late stages of pollen development, regulate maize pollen development with additive effect. ZmSTK1 or ZmSTK2 mutation exhibited severe pollen transmission deficiency, which thus influenced pollen fertility. Moreover, the kinase domains of ZmSTKs were cross‐interacted with C‐terminus of enolases detected by co‐immunoprecipitation (Co‐IP) and yeast two‐hybrid system (Y2H), respectively. Further, the detective ZmSTK1 or ZmSTK2 was associated with decreased activity of enolases and also reduced downstream metabolite contents, which enolases are involved in glycolytic pathway, such as phosphoenolpyruvate (PEP), pyruvate, ADP/ATP, starch, glucose, sucrose and fructose. This study reveals that ZmSTK1 and ZmSTK2 regulate maize pollen development and indirectly participate in glycolytic pathway.